Pengaruh Perhatian Orang Tua Terhadap Pembentukan Karakter Siswa SD - Didit Darmawan; Nur 'Aisyatir Rodliyah (Civiliza Publishing, Indonesia., 2026)
The phenomenon that occurs in elementary schools shows that there are still many students who face character problems, such as low discipline, responsibility, honesty, and social concern. This condition emphasizes the importance of the role of the family, especially the attention of parents, as the first and main environment in shaping children's character. This study aims to determine the influence of parental attention on the formation of the character of elementary school students. In this study using a qualitative method, this qualitative research uses a literature study approach. The results of the study show that parental attention has a significant effect on the formation of the character of elementary school students, so that the role of the family is proven to be a dominant factor in building children's personality and morals from an early age.